Behavior change theory, content and delivery of interventions to enhance adherence in chronic respiratory disease: A systematic review. (July 2016) - McCullough, Amanda R.; Ryan, Crístín; Macindoe, Christopher; Yii, Nathan; Bradley, Judy M.; O'Neill, Brenda; Elborn, J. Stuart; Hughes, Carmel M.
Abstract: Background: We sought to describe the theory used to design treatment adherence interventions, the content delivered, and the mode of delivery of these interventions in chronic respiratory disease. Methods: We included randomized controlled trials of adherence interventions (compared to another intervention or control) in adults with chronic respiratory disease (8 databases searched; inception until March 2015). Two reviewers screened and extracted data: post-intervention adherence (measured objectively); behavior change theory, content (grouped into psychological, education and self-management/supportive, telemonitoring, shared decision-making); and delivery. "Effective" studies were those with p < 0.05 for adherence rate between groups. We conducted a narrative synthesis and assessed risk of bias. Results: 12, 488 articles screened; 46 included studies (n = 42, 91% in OSA or asthma) testing 58 interventions (n = 27, 47% were effective). Nineteen (33%) interventions (15 studies) used 12 different behavior change theories. Use of theory (n = 11, 41%) was more common amongst effective interventions. Interventions were mainly educational, self-management or supportive interventions (n = 27, 47%). They were commonly delivered by a doctor (n = 20, 23%), in face-to-face (n = 48, 70%), one-to-one (n = 45, 78%) outpatient settings (n = 46, 79%) across 2–5 sessions (n = 26, 45%) for 1–3 months (n = 26, 45%). Doctors delivered a lower proportion (n = 7, 18% vs n = 13, 28%) and pharmacists (n = 6, 15% vs n = 1, 2%) a higher proportion of effective than ineffective interventions. Risk of bias was high in >1 domain (n = 43, 93%) in most studies. Conclusions: Behavior change theory was more commonly used to design effective interventions. Few adherence interventions have been developed using theory, representing a gap between intervention design recommendations and research practice.